2013
DOI: 10.1109/tdei.2013.6633703
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition characteristics of SF6 under partial discharges with point-to-plane electrode defect

Abstract: Field experience shows that the long-term existence of the partial discharge (PD) in gas-insulated switchgear (GIS) will gradually erode the insulation and ultimately cause disastrous insulation breakdown. The decomposition compound analysis of SF 6 in GIS is an effective method to diagnose the PDs caused by insulation defects. It is significant to clarify the decomposition characteristics of SF 6 under PDs, which is common in GIS. In this paper the discharge energy/charge and SF 6 decomposition under PDs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 26 publications
(50 reference statements)
2
5
0
Order By: Relevance
“…It turns out that under all discharging voltages, the concentrations increase over time, while a higher voltage always leads to a higher concentration for a specific discharging time. The similar trend has been observed by Ding et al 19 They found that the SOF 2 and SO 2 F 2 decomposition products increase linearly with the accumulation of partial discharge energy. During the discharge, the strong interaction of highenergy electrons with SF 6 causes their rapid deceleration to the lower energy of electron capture and dissociative attachment.…”
Section: Influence Of Discharging Voltage and Gas Pressure On The supporting
confidence: 88%
“…It turns out that under all discharging voltages, the concentrations increase over time, while a higher voltage always leads to a higher concentration for a specific discharging time. The similar trend has been observed by Ding et al 19 They found that the SOF 2 and SO 2 F 2 decomposition products increase linearly with the accumulation of partial discharge energy. During the discharge, the strong interaction of highenergy electrons with SF 6 causes their rapid deceleration to the lower energy of electron capture and dissociative attachment.…”
Section: Influence Of Discharging Voltage and Gas Pressure On The supporting
confidence: 88%
“…The applied voltage and frequency are 30 kV and 50 Hz respectively. Ding et al [21] has recorded the repetition rates of individual discharge pulses for corona and sparks at different pressures, finding that the repetition rate of corona discharge pulses at 0.4 MPa is 2869/s, i.e. 57 pulses per cycle for 50 Hz voltage frequency.…”
Section: Charged Speciesmentioning
confidence: 99%
“…Zeng et al studied the effects of trace water and oxygen on the concentrations of SOF 2 and SO 2 F 2 in a 50 Hz ac point-plane partial discharge and concluded that both H 2 O and O 2 have a more obvious influence on SOF 2 than on SO 2 F 2 [19,20]. Ding et al investigated the influence of the H 2 O content on the concentrations of SOF 2 , SO 2 F 2 and SO 2 in a 50 Hz ac point-plane corona discharge [21,22] and found that SO 2 could only be detected when the moisture content is higher than 1600 ppm and that the SO 2 yield increased with moisture content. Zhang et al reported that carbon nanotube arrays and TiO 2 nanotube arrays, which possess good sensing behavior towards SF 6 -decomposition species, are novel materials that can potentially be exploited as gas sensors for insulation evaluation in SF 6 devices [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the potential SF 6 decomposition species are significantly impacted by the content of H 2 O inside a device. , Up to now, many studies have been conducted to analyze the influence of H 2 O on the SF 6 decomposition mechanism under AC PD. Refs revealed that the generation of SO 2 F 2 and SOF 2 would be facilitated with the increase of the H 2 O content.…”
Section: Introductionmentioning
confidence: 99%